Abel Velásquez: a contribution to the Cajamarcan guitar - Díaz Oré, Jinet Ambar (2017)
A pioneering book has recently been published in the field of traditional Cajamarcan music by the musician and researcher Abel Velásquez, whose title is "Guitarra cajamarquina de concierto" (Cajamarcan Concert Guitar). It was presented at the facilities of the National Library of Peru with great reception. The days after said event, at the initiative of the National Conservatory of Music of Peru, we were presented with the opportunity to arrange an interview with maestro Abel. The conversation was motivated by the publication of the aforementioned book, however, once it began we could not help but investigate a little more about the training of its author, a training that is marked by a transition from the academy to the popular, that is, how a student of academic training at the Conservatory is motivated to venture into the popular field.